The effectiveness of cramer's rule in improving mathematical thinking skills and learning outcomes in solving systems linear equation of fixed pulley - Bambang Supriadi; Sisilia Nur Hikmah Anggraeni; Nurul Yunda Nanik Purwanti; Emma Berliana Pujiningtyas; Dina Mahartika (Universitas PGRI Kanjuruhan Malang, 2025)
Learning innovation is needed to make the learning process more attractive and improve student learning outcomes. Learning outcomes can be improved by making learning more interesting and developed according to student needs. Learning materials are packaged with different problem-solving methods that make learning more interesting to improve student learning outcomes. Based on existing findings, students' mathematical thinking skills are still relatively low. This study aims to measure the effectiveness of applying Cramer's rule to improve mathematical thinking skills and learning outcomes. This study uses a quantitative descriptive method which was carried out at Jember State High School and the Physics Education Study Program, Jember University in the odd semester of the 2024/2025 academic year. The results of data analysis from mathematical thinking skills affect the success of physics learning. The results of the homogeneity test and normality test that have been carried out show that the samples used are homogeneous and normal. The N-Gain value is obtained in the high category for improving mathematical thinking skills and learning outcomes. And the student response is very positive towards the use of Cramer's rule in solving the system of linear equations on the fixed pulley material. So it can be concluded that Cramer's rule in solving linear equation systems on pulley material remains effective in improving mathematical thinking skills and learning outcomes.